2019
DOI: 10.21776/ub.jam.2019.017.02.18
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Electronic Word of Mouth (Ewom), Brand Image, and Price on Re-Purchase Intention of Airline Customers

Abstract: This research aims to investigate the factors which influence the Citilink customer's repurchase intention. This research implements Electronic Word of Mouth (eWOM), brand image, and price as the independent variables that influence customer's repurchase intention. This research applies explanatory research, and the data are collected by employing a survey method. The respondents comprised 180 customers who had purchased Citilink Indonesia minimum in one purchased. The research data and hypothesis are analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
37
0
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 25 publications
7
37
0
16
Order By: Relevance
“…Repurchase Intention is part of consumer buying behavior where the match between the performance of the product or service offered by the company generates consumer interest to consume it again in the future (Wijaya in Apriyani and Suharti, 2017). Repurchase Intention is also a subjective probability that someone will buy a product or service continuously from an electronic supplier or store in the future (Yan and Yu in Arif, 2019). Meanwhile, according to Hellier in Juwiriyah (2019) that repurchase intention is to buy another product or service appointed from the same company by considering the previous situation with the current situation.…”
Section: Repurchase Intentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repurchase Intention is part of consumer buying behavior where the match between the performance of the product or service offered by the company generates consumer interest to consume it again in the future (Wijaya in Apriyani and Suharti, 2017). Repurchase Intention is also a subjective probability that someone will buy a product or service continuously from an electronic supplier or store in the future (Yan and Yu in Arif, 2019). Meanwhile, according to Hellier in Juwiriyah (2019) that repurchase intention is to buy another product or service appointed from the same company by considering the previous situation with the current situation.…”
Section: Repurchase Intentionmentioning
confidence: 99%
“…Repurchase Intention is a consumer commitment that is formed after a consumer makes a purchase of a product or service where this commitment arises from the consumer's positive impression of a brand and satisfying consumption of the purchase (Hicks et al, in Arif, 2019). To increase repurchase interest, a positive E-WOM (Electronic Word of Mouth) is needed.…”
Section: Introductionmentioning
confidence: 99%
“…It helps customers differentiate the brand and identified what kind of brand they need or want [6]. For the research related to low-cost carrier airline, Arif (2019) concluded that eWOM and brand image have a positive influence on customer's repurchase intentions of Indonesian airlines [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kunja and GVRK (2018) specified that interactions of the social media amongst the customers generate a constructive link between eWOM and consumers' purchase intention. Similarly, study done by Arif (2019), pointed out that eWOM and brand images are noticeable and positively affect the intent of customers' purchases. Likewise, Gruena, Talai, Osmonbekov and Czaplewskia (2006), suggested that customers realize the effects of eWOM on the customers' view of the product values and the likelihood to recommend the product, but does not affect the intention of consumer buying behaviour.…”
Section: Literature Review Online Customer Review (Ocr)mentioning
confidence: 89%